ISSN: 1693-9050 E-ISSN: 2623-1417 https://jurnal.polsri.ac.id/index.php/kimia/index 20 PENGARUH DAYA MICROWAVE DALAM PROSES PENGOLAHAN MINYAK MAWAR (Rosa hybrida) DAN MINYAK YLANG-YLANG (Cananga odorata genuine) DENGAN METODE MICROWAVE HYDRODISTILLATION - Effendy, Sahrul; Aswan, Arizal; Ridwan, K.A; ., Zurohaina; Ramadhania, Nadhira; Amanda, Thalia Junica (Politeknik Negeri Sriwijaya, 2020)
Rose and ylang-ylang flower oil is usually obtained by conventional hydrodistillation and takes a long time. One of the new technologies that can be used is hydro distillation using a microwave. This study aims to study the effect of time and microwave power on the yield of essential oils obtained and will be analyzed with rose oil standards ISO 9842: 2003 and CAS 8007-01-0 and ylang-ylang flower oil SNI 06-7224-2006. The variables tested in this study were the ingredients of rose and ylang-ylang flowers (fresh and wilted), weighing 200 grams and 100 grams, respectively. The microwave power used is 180, 270, 360, 450 Watt. The operating conditions in this method are at 1 atm. The highest yield of rose flower oil yield was at the power of 450 Watt minutes to 90 of 0.1266%, while the highest yield of ylang-ylang flower oil was at power of 360 watts to 90 minutes of 0.2758%. The lowest value of specific energy consumption (SEC) in roses is at a power of 450 watts of 2.0574 kWh / gr. The SEC value of ylang-ylang flower oil is at a power of 360 watts of 2.1318 kWh / gr.